Analysis of Thyroid Gland Problems with Shear Wave Elastography in Children with Celiac Disease - Basaran, Meryem K.; Gurkan, Okan (Current Medical Imaging, 2022)
Background: The rate of autoimmune thyroiditis in children with celiac disease (CD) is high relative to the normal population. Since the majority of these patients are also euthyroid, thyroid imaging methods are gaining significance in diagnosis and follow-up. This study examines the effectiveness of thyroid ultrasonography (US) and thyroid shear wave elastography (SWE) in diagnosing thyroid disease in children with CD. Materials and Methods: This cross-sectional controlled study analyzed thyroid US, SWE, serum thyroid function tests, and thyroid autoimmune antibodies of 106 CD patients and 103 control patients without CD. An Aplio 500 ultrasound device with a linear array transducer and elastography software was used for thyroid US and SWE measurement of all patients. Results: Right lobe thyroid volume, left lobe thyroid volume, total thyroid volume, thyroid mean elasticity (m/s), right lobe elasticity (kPa), left lobe elasticity (kPa), and mean thyroid elasticity (kPa) levels of the CD group were higher than those of the control group (p < 0.001). The relationships between thyroid US and thyroid mean elasticity (m/s), thyroid mean elasticity (kPa), anti-thyroid peroxidase antibody, and thyroid-stimulating hormone were positive and moderate, respectively (r = 0.612, 0.612, 0.636, and 0.565, respectively; p < 0.001). Conclusion: In this study, SWE findings were compatible with laboratory findings, as they constituted a sensitive and useful method in the diagnosis and follow-up of autoimmune thyroid disease in children with CD.
Keywords: celiac disease